MODELING OF THE TRAINING PROCESS AIMED AT DEVELOPING OFFENSIVE ACTIONS OF STUDENT BASKETBALL PLAYERS - KOTLOV Egor Viktorovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article examines current issues of attacking actions formation in student basketball. The modern practice of basketball players training is analyzed, the importance of developing tactical thinking, speed and coordination abilities is emphasized. The importance of modernization of the educational and training process, introduction of innovations and special methods for increasing the eﬀectiveness of attacking actions and the overall level of the game is determined. The obtained results can be used to optimize the educational and training process and introduce innovative approaches to the formation of professional qualities of future athletes.